2014
DOI: 10.1038/jhh.2014.33
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of plasma aldosterone and arterial stiffness in obese pre- and stage1 hypertensive subjects after aerobic exercise

Abstract: Obesity-related hypertension is associated with increased activity of the renin-angiotensin-aldosterone system (RAAS), increasing arterial stiffness. Aerobic exercise decreases pulse wave velocity (PWV), therefore a treatment option for hypertension and obesity. Assess RAAS activity and PWV before and after 4 weeks of aerobic training in unmedicated, pre-to-stage-1 hypertensives. Ten obese subjects (52±3.2 years, body mass index=33.5±1.4) performed 30 min of aerobic exercise on a treadmill 3 days per week at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…16 Increasing evidence of a role for aldosterone and MR signaling in development of arterial stiffness has emanated from multiple studies. 1720 A recent clinical study reported an association between elevated serum aldosterone concentrations and increased aortic stiffening in normotensive overweight and obese adults aged 20 to 45 years. 21 Moreover, accumulating evidence suggests improvement in arterial elasticity occurs with administration of MR antagonists (MRA).…”
Section: Introductionmentioning
confidence: 99%
“…16 Increasing evidence of a role for aldosterone and MR signaling in development of arterial stiffness has emanated from multiple studies. 1720 A recent clinical study reported an association between elevated serum aldosterone concentrations and increased aortic stiffening in normotensive overweight and obese adults aged 20 to 45 years. 21 Moreover, accumulating evidence suggests improvement in arterial elasticity occurs with administration of MR antagonists (MRA).…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic exercise reduces blood pressure in hypertension people with central obesity due to the decrease of plasma aldosterone and pulse wave velocity that causes vasodilation (Collier et al, 2015). High intensity interval training (HIIT) induces an improvement in blood pressure through the dilatation process of blood vessels, thereby the blood flow to muscles increases along with the increase of exercise intensity and the regulation of the nervous system and hormones in form of decreased norepinephrine levels at rest (Ciolac et al, 2010;Ciolac et al, 2011;Ramos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies analyzing the relationship between aldosterone and physical activity have been inconclusive. Some studies reveal that physical activity in the form of aerobic exercise decreases aldosterone levels [42,43], while others have shown no effect of aerobic exercise on aldosterone [44,45]. Interestingly, there may be racial/ethnic differences with one study revealing lower aldosterone after aerobic exercise training among whites but not AAs [44].…”
Section: Discussionmentioning
confidence: 99%